Water-mass evolution in the Cretaceous Western Interior Seaway of North America and equatorial Atlantic - Eldrett, James S.; Dodsworth, Paul; Bergman, Steven C.; Wright, Milly; Minisini, Daniel (Climate of the Past, 2018)
The Late Cretaceous Epoch was characterized by major global perturbations in the carbon cycle, the most prominent occurring near the Cenomanian–Turonian (CT) transition marked by Oceanic Anoxic Event 2 (OAE-2) at 94.9–93.7 Ma. The Cretaceous Western Interior Seaway (KWIS) was one of several epicontinental seas in which a complex water-mass evolution was recorded in widespread sedimentary successions. This contribution integrates new data on the main components of organic matter, geochemistry, and stable isotopes along a north–south transect from the KWIS to the equatorial western Atlantic and Southern Ocean. In particular, cored sedimentary rocks from the Eagle Ford Group of west Texas (∼ 90–98 Ma) demonstrate subtle temporal and spatial variations in palaeoenvironmental conditions and provide an important geographic constraint for interpreting water-mass evolution. High-latitude (boreal–austral), equatorial Atlantic Tethyan and locally sourced Western Interior Seaway water masses are distinguished by distinct palynological assemblages and geochemical signatures. The northward migration of an equatorial Atlantic Tethyan water mass into the KWIS occurred during the early–middle Cenomanian (98–95 Ma) followed by a major re-organization during the latest Cenomanian–Turonian (95–94 Ma) as a full connection with a northerly boreal water mass was established during peak transgression. This oceanographic change promoted de-stratification of the water column and improved oxygenation throughout the KWIS and as far south as the Demerara Rise off Suriname. In addition, the recorded decline in redox-sensitive trace metals during the onset of OAE-2 likely reflects a genuine oxygenation event related to open water-mass exchange and may have been complicated by variable contribution of organic matter from different sources (e.g. refractory/terrigenous material), requiring further investigation.